NARASI TENTANG AUTISM DI FACEBOOK (Studi Autoetnografi pada Status K.W) - Kusumastuti, Frida; Leonardo, Jeanne; Widiatmojo, Radityo (Interaksi: Jurnal Ilmu Komunikasi, 2019)
The narrative of a mother who is directly involved in living with a child with an autistic child's lifetime is worth noting because it can complement the narrative of the Professionals (doctors, psychiatrists, psychologists, educators). Especially if the narrative is done openly on social media such as Facebook. Social Media gives the opportunity of public voices that were originally being repossessed by large narratives. Thus the purpose of this research is to interpret the narrative of the subject about autism based on daily experience (everyday life). Narrative is the way someone tells his experience. The narrative about Autism, commonly referred to as "disability", is not necessarily the same as the people's narration or family. The narrative of experts and the general public about defects is often done in a dichotomistic, i.e. only when defects – including autism – are seen as sadness or suffering, and when a defective individual is successful with extraordinary achievement. This research was conducted on a Facebook social account, which is a KW account – a single-parent mother claiming to have five children, of which three of them (15 years old, 10 years old and 7 years old) were autistic. The choice on the subject of the study because the KW handled the children's autism with a full involvement with no shadower nor professional caregiver. Secondly, KW is capable of conducting autism narrative through social media (Facebook) which is open. The results showed (1) Narrative about the nature, attitudes, and principles of Autism, (2) narrative on the achievement of autism.